Digital Transformation of Islamic Education: AI, Gamification, and Pedagogical Adaptation for Generation Z - Norman, Efrita; Enah Pahlawati; Muhammad Lanri Siregar; Dessy Damayanthy (Pascasarjana Universitas Islam Negeri Raden Fatah Palembang, 2025)
Islamic education is undergoing a significant transformation due to rapid technological advancements and the learning preferences of Generation Z. Traditional methods such as memorization, halaqah, and talaqqi remain fundamental, yet digitalization is becoming increasingly necessary to maintain engagement and relevance. This study aims to explore the integration of artificial intelligence and gamification into Islamic education, particularly in madrasahs, Islamic boarding schools, and modern Islamic schools in Bogor. Using a mixed methods approach, qualitative data were collected through in-depth interviews and observations, while quantitative data were gathered from surveys involving students, educators, and parents. The findings reveal that while modern Islamic schools have embraced digital learning, madrasahs and Islamic boarding schools face challenges in digital adoption due to resistance from educators, lack of infrastructure, and concerns over maintaining traditional values. Statistical analysis indicates no significant correlation between digital learning preferences and students’ understanding of Islamic values, highlighting the need for a structured approach to digital integration. This study contributes to the field by proposing a hybrid learning model that combines traditional pedagogies with AI-driven personalized learning and interactive gamification techniques. While offering a framework for digital transformation in Islamic education, this study acknowledges limitations, including its focus on a single geographic region and the need for further research on the long-term effects of AI in religious education. Moving forward, strategic policies, educator training, and infrastructure development are essential to ensure that digitalization enhances, rather than compromises, the integrity of Islamic education.